Measuring the Reliability of Wheelchair User Route Planning based on Volunteered Geographic Information. Issue 2 (17th April 2014) - Neis, Pascal
Abstract The development of a wheelchair user friendly route planning application inherits a number of special requirements and details that need to be considered during the generation of the routing graph and the corresponding algorithm, making this task much more complex than car or pedestrian related applications. Each wheelchair type and, more importantly, each individual user might have different needs with regards to the way condition or other criteria. This study proposes a new approach to route planning for wheelchair users tailored for individual and personal requirements provided by the user and the calculation of a reliability factor of the computed wheelchair path. The routing graph is based on the freely available Volunteered Geographic Information (VGI) retrieved from the OpenStreetMap (OSM) project. The newly created algorithm is evaluated and tested for a selected area in Bonn, Germany. A new reliability factor is introduced that gives direct feedback about the quality of the generated path. Similar factor estimations can also be utilized for multiple route planning applications where VGI or other commercial or administrative data is implemented and more detailed factors than a simple geometric representation of a street network are of importance.